Review of Lasers and Energy-Based Devices for Skin Rejuvenation and Scar Treatment With Histologic Correlations. Issue 4 (11th April 2022) - Chen, Stella X.; Cheng, Judy; Watchmaker, Jacqueline; Dover, Jeffrey S.; Chung, Hye Jin
Abstract : Supplemental Digital Content is Available in the Text. Abstract : BACKGROUND: Lasers and energy-based devices (EBD) are popular treatments for skin rejuvenation and resurfacing. Achieving desired outcomes and avoiding complications require understanding the effects of these devices at a histologic level. Currently, no comprehensive review summarizing the histologic effects of laser and energy-based treatments exists. OBJECTIVE: To describe how lasers and EBD alter skin histology and improve the overall understanding of these devices. MATERIALS AND METHODS: A PubMed search was conducted for studies with histologic analysis of fractional picosecond laser, fractional radiofrequency microneedling, nonablative lasers, and ablative lasers. RESULTS: Fractional picosecond lasers induce intraepidermal and/or dermal vacuoles from laser-induced optical breakdown. Fractional radiofrequency microneedling delivers thermal energy to the dermis while sparing the epidermis, making it safer for patients with darker skin phototypes. Fractional nonablative lasers induce conical zones of coagulation of the epidermis and upper dermis. Ablative lasers vaporize the stratum corneum down to the dermis. Traditional ablative lasers cause diffuse vaporization while fractional ablative lasers generate columns of tissue ablation. CONCLUSION: Lasers and EBD are effective for skin resurfacing and rejuvenation and have different mechanisms with disparate targets in the skin. Safe and effective use of devices requires understanding the histologic laser–tissue interaction.